2023
DOI: 10.2147/rmhp.s420899
|View full text |Cite
|
Sign up to set email alerts
|

How National Health Insurance Coverage Policy Affected the Use of Trastuzumab and Rituximab in China: A Bicentric Retrospective Study

Linlin Shang,
Yingtao Lin,
Wenqing Fang
et al.

Abstract: Background: Cancer is a significant health concern and is China's leading cause of mortality. Targeted therapies, such as trastuzumab and rituximab, have enhanced clinical treatment efficacy. However, their high costs burden patients and healthcare systems considerably. Patient demographic factors further influence the utilization of these expensive drugs. On September 1, 2017, China implemented the National Health Insurance Coverage (NHIC) policy, necessitating additional real-world evidence to assess its imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…A signi cant increase in Trastuzumab utilization was observed following the introduction of basic medical insurance coverage and the price reduction, which is consistent with ndings from studies conducted in other Chinese provinces [16,26,35]. Our study found that the level of medical insurance coverage is the only factor in uencing Trastuzumab utilization in JX city.…”
Section: Affordability As a Key Determinant Of Trastuzumab Utilizationsupporting
confidence: 90%
See 1 more Smart Citation
“…A signi cant increase in Trastuzumab utilization was observed following the introduction of basic medical insurance coverage and the price reduction, which is consistent with ndings from studies conducted in other Chinese provinces [16,26,35]. Our study found that the level of medical insurance coverage is the only factor in uencing Trastuzumab utilization in JX city.…”
Section: Affordability As a Key Determinant Of Trastuzumab Utilizationsupporting
confidence: 90%
“…This is similar to the ndings by Shang, indicating that HER2-positive patients covered by both UEBMI and URRBMI didn't show signi cant differences in Trastuzumab usage. Instead, the crucial determinant was the availability of basic medical insurance coverage in 2017 [35]. Furthermore, our study revealed a signi cant rise in utilization rates, reaching approximately 90% from 2020 to 2022 after a price reduction in 2020.…”
Section: Affordability As a Key Determinant Of Trastuzumab Utilizationmentioning
confidence: 63%
“…Secondly, Chinese hospitals implement the strict medical technology charging standards, and most of the charging standards have not been adjusted for a long time, while the prices of drugs and medical consumables are widely influenced by the regulation of the market, and have been on a rising trend in recent years. 31 , 32 As a result, the surgery expenses in Chinese hospitals are underestimated, while the drug expenses usually account for a relatively high proportion.…”
Section: Discussionmentioning
confidence: 99%